2020
DOI: 10.1186/s42494-020-0010-x
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence, characteristics and outcome of seizure in tuberculous meningitis

Abstract: Seizures are a common finding in patients with tuberculous meningitis (TBM), and associate with four times increased risk of death and neurological disability, especially in children. It has been reported that brain inflammation, diffuse neuronal injury, and reactive gliosis may all contribute to the pathogenesis of seizures in TBM. Early seizure onset may be associated with meningeal irritation and cerebral oedema; while, the late seizures are usually due to infarction, hydrocephalus, tuberculoma and paradoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
14
1
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 100 publications
3
14
1
9
Order By: Relevance
“…In this work, by analyzing HD and TB patients' plasma, we found that TB patients exhibit significantly higher concentrations of PGE2 as compared to HD (Figure 1). This observation is in agreement with other works reporting a greater amount of PGE2 in cerebrospinal fluid from meningeal TB patients compared to control individuals 19 . In turn, Mayer-Barber et al also observed higher concentrations of PGE2 in plasma from patients with mild TB as compared to HD and, additionally, extended this result taking into account the relationship with the production of another eicosanoid, such as LXA-4 10 .…”
Section: Discussionsupporting
confidence: 94%
“…In this work, by analyzing HD and TB patients' plasma, we found that TB patients exhibit significantly higher concentrations of PGE2 as compared to HD (Figure 1). This observation is in agreement with other works reporting a greater amount of PGE2 in cerebrospinal fluid from meningeal TB patients compared to control individuals 19 . In turn, Mayer-Barber et al also observed higher concentrations of PGE2 in plasma from patients with mild TB as compared to HD and, additionally, extended this result taking into account the relationship with the production of another eicosanoid, such as LXA-4 10 .…”
Section: Discussionsupporting
confidence: 94%
“…1). Our ndings are in line with other works reporting greater amounts of PGE2 in cerebrospinal uid from meningeal TB patients as compared to control individuals 24 . Moreover, Mayer-Barber et al also observed higher concentrations of PGE2 in plasma from patients with mild TB as compared to HD and even extended this result considering the ratio with LXA-4 production 6 .…”
Section: Discussionsupporting
confidence: 93%
“…The collected data indicated that one of the most important causes of seizures due to central nervous system infection is in ammation of the brain and nerve damage and the reactivation of glial cells (14).…”
Section: Discussionmentioning
confidence: 99%